P-699 Women with increased risk for hereditary breast and/or ovarian cancer do not have diminished ovarian reserve. (30th June 2022) - Sighinolfi, G; Imbrogno, M.G; Grandi, G; Toss, A; Barbieri, E; Razzaboni, E; La Marca, A
Abstract: Study question: Does ovarian reserve, measured with antimullerian hormone (AMH) and antral follicle count (AFC) diminish in BRCA, CHEK2, PALB2, RAD50, RAD51D, ATM, TP53 pathogenic variants carriers? Summary answer: Ovarian reserve, measured with antimullerian hormone (AMH) and antral follicle count (AFC) doesn't diminish in women with increased risk for hereditary breast and ovarian cancer What is known already: Besides the concerns for increased cancer risk, women carrying a predisposing mutation for breast and ovarian cancer face several non-oncological issues that affect the quality of their reproductive lives. Particularly, in recent literature, it remains controversial whether carriers of these mutations, in comparison with non-carrires, have lower ovarian reserve, tendencies to experience premature menopause and lower ovarian response to ovarian stimulation Study design, size, duration: This was the first prospective single-center study and was performed between July 2020 and December 2021. All women carrying a germline mutation of BRCA 1/2, CHEK2, PALB2, RAD50, RAD51D, ATM, TP53 under the age of 42 with no history of previous chemotherapy and/or ovarian surgery were eligible. We enrolled 55 women with these germline mutations Participants/materials, setting, methods: On the day in which patients were recruited, a blood sample was obtained by venipuncture to determine the antimullerian hormone (AMH) level, independent from the last menstrual cycle. Serum AMH was measured by the new automated Access AMH assay (Beckman Coulter). Thereafter, a transvaginal ultrasound was performed by a single operator to evaluate antral follicle count (AFC) Main results and the role of chance: We defined low ovarian reserve as having AMH<1 ng/ml and AFC<7. Only 5/55 (9%) of the study group had an AMH<1 ng/ml and only 4/55 (7.3%) had an AFC<7. In our study population the distribution of AMH percentiles was as follows: only 3/55 (5.5%) had an AMH< 10th percentile by age, 5/55 (9.1%) had AMH values between 10th and 25th percentile, 12/55 (21.8%) between 25th and 50th percentile, 14/55 (25.5%) between 50th and 75th percentile, 13/55 (23.6%) between 75th and 90th percentile and 8/55 (14.5%) above 90th percentile. This means that 47.3% (26/55) of the women had an AMH between the 25th and 50th percentile and 32.7% (18/55) had an AFC between the 25th and 50th percentile. Most of the women studied had an ovarian reserve above the median: 35/55 (corresponding to 63.6%) for AMH and 44/55 (corresponding to 80%) for AFC. The results obtained are consistent with the normal curves of the general population, showing that ovarian reserve in women with germline mutations of BRCA 1/2, CHEK2, PALB2, RAD50, RAD51D, ATM, TP53 is not reduced compared to that of the general population. Limitations, reasons for caution: The limitation of the study is the small sample size. Further prospective studies should be done to confirm the finding that women with germline mutation of BRCA 1/2, CHEK2, PALB2, RAD50, RAD51D, ATM, TP53 have a normal ovarian reserve. Wider implications of the findings: Women with germline mutations of BRCA 1/2, CHEK2, PALB2, RAD50, RAD51D, ATM, TP53 should be advised that their ovarian reserve is normal. However, there is still a need for adequate counselling to encourage women to have their pregnancies at an early stage, before any potential disease onset and/or prophylactic surgery. Trial registration number: GR-2018-12367239